Nutrient allocation patterns in different aboveground organs at different reproductive stages of four introduced Calligonum species in a common garden in northwestern China - Liu, Ji-Yuan; Zhang, Xue-Lian; Jin, Xin-Yue; Wang, Meng-Ting; Zhang, Yuan-Yuan; Wang, Xi-Yong (Frontiers in Plant Science, 2024)
Calligonum species are the typical shrubs with assimilative branches (ABs) in the arid regions in Central Asia. The nutrient distribution patterns at different reproductive stages are of great significance for further understanding their ecological adaptation and survival strategies of plants. In the present study, a common garden experiment was employed to avoid the interference from environmental heterogeneity. And then, the nitrogen (N), phosphorus (P), and potassium (K) allocation characteristics in the supporting organs (mature branches), photosynthetic organs (ABs), and reproductive organs (flowers and fruits) of Calligonum caput-medusae (CC), Calligonum arborescens (CA), Calligonum rubicundum (CR), and Calligonum klementzii (CK) during the flowering phase, unripe-fruit phase, and ripe-fruit phase were systematically analyzed. The results showed that aboveground organs were the main factors affecting the variation in N, P, and K concentrations and their stoichiometric ratios, and reproductive stages were secondary factors affecting N, P and P:K, and species were secondary factors affecting K, N:P, and N:K. Meanwhile, significant interactions were found for all of the three factors abovementioned. The N and P concentrations in ABs of the four species were highest during the flowering phase, while the N:P was the lowest; which then gradually decreased and increased during plant growth, respectively. This result supported the Growth Rate Hypothesis, i.e., the growth rate was highest during the early growth stage. In the growth period, the N, P, and K concentrations in each organ of the four Calligonum species followed the power law, with the allocation rates of N and P being generally higher than K. For different the species, the N−P scaling exponent in ABs of CR was only 0.256; according to the scaling exponent law, this species was the least stressed and had the strongest environmental adaptability. Overall, the adaptability of the four species ranked as CR > CA > CC > CK. In conclusion, there were significant differences in nutrient traits among different aboveground organs, species, and reproductive stages. The results of this study contribute to deeper understanding of the nutrient allocation strategies of different Calligonum species and provide scientific evidence for the ex-situ conservation and sand-fixing application of these species.